1986
DOI: 10.1128/jb.168.2.795-798.1986
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat-mediated selection for mutations in the manganese-superoxide dismutase gene sodA

Abstract: We report the unexpected result that Escherichia coli isolates containing a multicopy plasmid (pDT1.5) carrying the manganese-superoxide dismutase gene sodA were more sensitive than the wild type to paraquatmediated growth inhibition. The pDTl.5 locus responsible for the paraquat-sensitive phenotype was delimited to a 0.6-kilobase segment by transposon Tn5 mutagenesis. Moreover, superoxide dismutase activity was the same as in the wild type in strains carrying pDT1.5::TnS insertions mapping to the 0.6-kilobase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…1, 4, and 5) are consistent with several other reports. For example, detrimental rather than protective effects are observed with SOD overexpression in E. coli cells treated with a superoxide generator, paraquat (6,30). Since paraquat treatment increases superoxide levels (21), as does antimicrobial treatment (1,5), rapid conversion of excessive superoxide to H 2 O 2 by overexpressed SOD is likely to trigger lethal hydroxyl radical generation.…”
Section: Discussionmentioning
confidence: 99%
“…1, 4, and 5) are consistent with several other reports. For example, detrimental rather than protective effects are observed with SOD overexpression in E. coli cells treated with a superoxide generator, paraquat (6,30). Since paraquat treatment increases superoxide levels (21), as does antimicrobial treatment (1,5), rapid conversion of excessive superoxide to H 2 O 2 by overexpressed SOD is likely to trigger lethal hydroxyl radical generation.…”
Section: Discussionmentioning
confidence: 99%
“…Interest-ingly, we have found that if cells are stressed by a number of agents (including heat), catalase in the medium will give higher colony counts (unpublished); H202 may be a common product of generalized cellular stress [Ames, 1983;Hartman, 1986;Richter and Loewen, 1981;Tyrrell, 1985;Vassilyadi and Archibald, 1985;Winguest et al, 19841. Superoxide dismutase (SOD) is a logical candidate as a NUV-recovery enzyme [Ahmad, 1981;Farr et al, 19861. We have found that the presence of a plasmid carrying an inducible Mn-superoxide dismutase (sodA) [Bloch and Ausubel, 1986;Carlioz and Touati, 19861 endows the cell with some resistance to NUV, but not FUV. This is of interest since it implicates 0, as a lethal radical.…”
Section: Recovery From Nuv Damagementioning
confidence: 99%
“…Not only is there no correlation between NUV resistance and catalase activity, but in some cases the correlation is inverse. Mutants other than katF (ie, katE and katG') that are defective in catalase activity [Loewen, 1984;Loewen et al, 1983Loewen et al, , 1985a [Bloch and Ausubel, 1986; Carlioz and Touati, 19861 endows the cell with some resistance to NUV, but not FUV. This is of interest since it implicates 0, as a lethal radical.…”
mentioning
confidence: 99%
“…It should be noted that evidence in the literature supports the notion that overexpression of SOD can sensitize rather than protect cells from oxidative stress. For example, a 5-fold increase in Mn-SOD or a 10-fold increase in Fe-SOD sensitized E. coli to paraquat toxicity (43,44). While transfection of Cu,Zn-SOD into HeLa cells resulted in overall resistance to paraquat, the degree of protection was not proportional to the increase in enzyme activity (45).…”
Section: Dna Bkamentioning
confidence: 99%